Investigating cognate effects across different writing scripts: the case of brazilian portuguese-english-korean multilinguals - Carvalho, Luiza de Melo (2023)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2023.